Magnetic Levitation for Separation of Plastic Polyethylene Terephthalate (PET) and Polyvinyl Chloride (PVC) - Gancang Saroja; Suyatman Suyatman; Nugraha Nugraha (Natural B, Journal of Health and Environmental Sciences, 2012)
In the recycling of plastic waste, the process of plastic separation is often faced with the problem of the difficulty of separating PET from PVC plastics. The main objective of this research was to separate a mixed PET and PVC plastics using magnetic levitation. In the experiment, the samples were PET and PVC plastics from used bottles packaging found in the market. The magnetic field was derived from arrangement of the permanent magnets made from Neodymium with a cylinder shape with an orientation of magnetic moment parallel to its axis. Magnets were arranged so as to produce a magnetic field gradient in the vertical direction. The magnetic inductions at the respective surface of each magnet were 0.244, 0.349, 0.412, 0.443, 0.463, and 0.476 T. The paramagnetic fluid used was solution of MnCl2 with a concentration of 1, 1.5, 2, 2.5, and 3 M. The results showed that at Bo of 0,476 T, the fluid with the concentration of 3 M produced the highest levitation and the best separation of PET from PVC plastics.